TINJAUAN TERHADAP TINDAK PIDANA PERAMPASAN BERDASARKAN PASAL 368 KUHP DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA SAMARINDA - Ageng Prabowo (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTCrime of seizure is one of the most troubling social problems both with violence and with threats, so it needs to be prevented and known that the legal process applied in the crime of violence with the threat of violence and can cause a flaring effect and the number of cases of Deprivation can be reduced in society.The problems examined in this study are related to how the application of the material criminal law against criminal acts of deprivation according to article 368 of the Criminal Code, as well as the element of the material crime against article 368 of the Criminal Code can be fulfilled by the perpetrators. The purpose of this study is to know in-depth the reasons for the need for the application of material criminal law against criminal offenses according to article 368 of the Criminal Code and to find out whether the material criminal elements contained in Article 368 of the Criminal Code can be fulfilled by the perpetrators.Based on the results of the study, it was concluded that the application of criminal law against offenses deprivation and threats of violence against others, namely regulating theft, accompanied by violence/threats of violence carried out jointly, can be applied with article 368. That criminal acts as stipulated in Article 368 paragraph The Criminal Code concerning Deprivation with Threats must be proven by the actual surrender of part of the property or all of the property of another person to the contrary to his own will, due to violence or threats of violence. So that if these things can be met, the element of material crime in Article 368 of the Criminal Code can be fulfilled. Keywords: threatening, extortion. Robbery.